Remating in wild females of the Mediterranean fruit fly, Ceratitis capitata - Kraaijeveld, Ken; Katsoyannos, Byron I.; Stavrinides, Menelaos; Kouloussis, Nikos A.; Chapman, Tracey (My University, 2005)
Female remating is widespread among animal taxa, and shows high interspecific diversity in frequency. While there is no consensus on general explanations for why females mate multiply, it is clear that remating rate has important implications for many evolutionary processes such as sperm competition, cryptic female choice and sexual conflict. We investigated the refractory period and the effect of sex ratio on remating in wild-derived individuals of the Mediterranean fruit fly (medfly) Ceratitis capitata (Wiedemann) (Diptera, Tephritidae), an insect pest species of major worldwide economic importance. In addition, we determined the remating rates of wild females throughout the flying season. Experiments with medflies that were the offspring of wild flies showed that remating was frequent and was observed in 3.3-13.3% of females on each of the 4 days after the first mating. Many matings thus induce only a short refractory period. Again using the offspring of wild flies, we found that female remating increased significantly under a highly male-biased sex ratio. Microsatellite analysis of offspring from wild-collected females showed that remating is common (4-28% of offspring arrays showed multiple paternity) and occurred throughout the flying season of these insects. These results have important implications for insect pest management using the sterile insect technique. © 2004 The Association for the Study of Animal Behaviour. Published by Elsevier Ltd. All rights reserved.
Keywords: Tephritidae; Fruit flies; Wild males